Economic Integration, Wage Policies and Social Policies - Michael Pflüger (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper sets up a two country monopolistic competition model with intra-industry trade to study the effects of an exogenous differential in wage and social policies on the location of industry. Two model scenarios are considered. In the traditional one with physical capital, such a differential induces a relocation effect which increases with the level of trade integration. The ?new economic geography? world assumes mobile entrepreneurs which can relocate thus bringing agglomeration forces into play. The most significant difference between this world and the traditional one is that, at high levels of trade integration, where one country has emerged as the core and the other as the periphery, the core may have more generous social policies and higher wages than the periphery without inducing a relocation of firms. The scope to have higher wage is constrained, however, and related to the level of trade integration in a bell-shaped way.
Keywords: F16; F22; F15; F12; F21; R12; 330; Integration; wages; industry location; agglomeration; monopolistic competition; Wirtschaftsintegration; Industriestandort; Standorttheorie; Lohnpolitik; Sozialpolitik; Standortwettbewerb; Neue ökonomische Geographie; Monopolistischer Wettbewerb; Theorie